Nikorex Company / Muhamad Syahmi Mat Suud - Mat Suud, Muhamad Syahmi (2022)
This is an effort to make some use of the hypotheses. As a student in UiTM Perlis, Arau branch, it is a part of study for everyone to undergo a case study project. in the beginning of the study, many of the company's specific data has been obtained . Most of the information is gathered through the primary and secondary source as well. For this purpose, I had the chance to do extensive research on a company, which I am interested in developing my own project for NIKOREX company. This company is currently based in Masai, Johor where it has eleven outlets in Malaysia and one in Singapore. This section presents the detailed research of the specialist . Objective of the project is to work on the background, organizational structure, products and services that NIKOREX provides. Currently, the CEO of the company is Mr Desmond Teo. He was also assisted by director of operation, Chua Lily and senior business development executive, Haziq Ezwan. The NIKOREX has provides various product for the customer needs and has over 100 type daily necessities. In addition, I was studied about the technology of NIKOREX product, as well as the marketing, business and its operational strategy used by the company to promote their products which we find quite interesting. Business company and marketing strategies of NIKOREX are all permit offered across the globe, online shopping and social media. To Conclude, I have analysed and find the solution to overcome and to fulfil their needs and making it as my innovation to be continued in new Product Development task. All the solutions I have discuss it in the finding and discussion segment. In addition, I aim to enhance the satisfaction of customer when use the trolley and at the same time, increase sale for the company. The company also will be popular across the globe because of the innovation.